Host long non-coding RNAs during bacterial infection - Abha Sahni; Sanjeev K. Sahni (Academia Biology, 2025)
The emergence of long non-coding RNAs (lncRNAs) has precipitated a paradigm shift in molecular biology. These lengthy RNA molecules, exceeding 200 nucleotides, exhibit regulatory prowess, modulating cellular processes through intricate interactions with DNA, RNA, and proteins. Investigations into host lncRNAs’ immunological roles, particularly in the context of bacterial infections, have yielded valuable insights. This burgeoning field of research continues to elucidate the mechanisms underlying lncRNA-mediated immune responses. Host lncRNAs play a pivotal role during bacterial infections, influencing cellular pathways to orchestrate a robust defense. Unraveling their functional mechanisms and therapeutic potential is crucial for advancing our understanding. This review delves deeply into the role of lncRNAs in various aspects of bacterial infections, including their impact on cellular damage, immune responses, host–pathogen/microbiome interactions, drug resistance, and future research/clinical outcomes. The rapidly evolving field of lncRNA research holds promise for revolutionary breakthroughs in combating microbial infections, presenting a rich tapestry of avenues for future exploration and translational applications.